Campylobacter jejuni infection and IgE sensitization in up to 2-year-old infants - Jovanovic, Dara; Ilic, Nevenka; Miljkovic-Selimovic, Biljana; Djokic, Dragoljub; Relic, Tijana; Cambur, Zoran; Doder, Radoje; Kostic, Gordana (Vojnosanitetski pregled, 2015)
Background/Aim. The ?hygiene hypothesis? addresses the correlation between the occurrence of atopy and the frequency of infections in the earliest age, explaining an increase in the incidence of atopic diseases by living in good, infection-free, hygienic conditions. The aim of our study was to determine the conection between atopy and Campylobacter infection, and to analyze the association between serum concentrations of total IgE and Campylobacter infection in relation to atopy in children up to two years. Methods. A case control study was conducted with the sample of 98 infants of the average age of 8 months. Total serum IgE and Phadiatop infant multi-test were determined on Immunocap-100 (Phadia AB, Uppsala, Sweden). The presence of atopy was determined by detection of serumspecific IgE ? 0.35 kUA/L (Phadiatop infant positive) and serum IgM, IgA, IgG levels against C. jejuni were determined by a quantitative immuno-enzyme test - SERION ELISA classic. Results. Total IgE cut-off values ? 15 kU/L point to atopy in infants, and tIgE cut-off values ? 8.1 kU/L pointed to a C. jejuni infection in infants. Within the group of atopic children, tIgE levels ? 29.8 kU/L point to C. jejuni infection, and within the group of non-atopic children, tIgE levels ? 5.9 kU/L point to infection. Enteritis is not a predictor of C. jejuni infection, because of a high frequency of asymptomatic cases of infection. The risk factors for C. jejuni infection are age and tIgE, and the protective factors are breastfeeding and atopy. Conclusion. C. jejuni infection increases the total serum IgE level, which is predictive of infection, regardless of the presence of atopy. The presence of symptomatic C. jejuni infection reduces the risk of atopy in a child of the age of 5-24 months by the factor of 10. nema